Uninvited guests: flesh fly maggots as accidental parasites in the intestines of a common wall lizard - A. Alvaro; L. Sanchez-Ruiz; I. Varotto-Boccazzi; G. Naro; P. Gabrieli (The European Zoological Journal)
Myiasis refers to the infestation of vertebrates, including humans, by the larvae of Diptera. This condition can affect various parts of the host’s body, where the larvae feed, including the gastrointestinal tract. In cases of intestinal myiasis, obligate parasitic fly larvae complete the development up to the pupal stage within the host’s gastrointestinal system. Other fly species, typically free-living, can cause opportunistic infestations in the gastrointestinal tract, leading to a condition known as pseudomyiasis or accidental intestinal myiasis. Here, we present a potential case of gastrointestinal infestation in a male of Podarcis muralis, the common wall lizard, by larvae of Sarcophaga carnaria. The lizard was found dead with a swollen abdomen, and upon dissection, 28 maggots were recovered from its intestines. The larvae were intact and arranged longitudinally, with one found near the cloacal opening. To the best of our knowledge, this is the first reported case of intestinal myiasis in a reptile.